Utilizing Mindfulness as an Evening Reflection at Residential Camp - Heather M. Janney (EDIS)
Utilizing mindfulness as an evening reflection at residential camps has been developed as a tool for use at the end of the day during residential camps, though language may be modified for use at the end of classes or day camps. The four lessons in this new 7-page publication of the UF/IFAS Florida 4-H Youth Development Program, written by Heather Janney, were developed as a way for youth to reflect on their activities throughout the day. It is recommended to do only one lesson 15-20 minutes per day. https://edis.ifas.ufl.edu/4h412